Cloning of a hemolysin gene from Leptospira interrogans serovar hardjo. - del Real, G (1989)
A DNA fragment encoding both hemolysin and sphingomyelinase C activity was cloned from the pathogenic bacterium Leptospira interrogans serovar hardjo. Initial clones were obtained by screening a genomic library in EMBL3 for hemolytic activity. Both hemolytic and sphingomyelinase C activities were coded for by a 3.9-kilobase BamHI fragment. The hemolysin was expressed from its own promoter in Escherichia coli K-12. Similar DNA sequences were also present in the serovars tarassovi and ballum.